Preclinical evaluation of the ROCK1 inhibitor, GSK269962A, in acute myeloid leukemia - Pan, Ting; Wang, Sijia; Feng, Hao; Xu, Jiawen; Zhang, Miao; Yao, Yao; Xu, Kailin; Niu, Mingshan (Frontiers in Pharmacology, 2022)
Acute myeloid leukemia (AML) is an aggressive hematologic malignancy with high mortality that urgently requires new treatments. ROCK1 plays an essential role in regulating growth and survival in AML cells. In this study, we evaluated GSK269962A, a selective ROCK1 inhibitor, in preclinical models of AML. Compared with solid tumors, GSK269962A selectively inhibited cell growth and clonogenicity of AML cells. Furthermore, GSK269962A arrested AML cells in the G2 phase and induced apoptosis by regulating multiple cell cycle- and apoptosis-associated proteins. Strikingly, GSK269962A could eliminate leukemia cells from bone marrow, liver, and spleen in an animal model of AML and significantly prolong mouse survival. Mechanistically, GSK269962A could inhibit the growth of AML by blocking ROCK1/c-Raf/ERK signaling pathway. Notably, a correlation was found between the expression levels of ROCK1 protein and the sensitivity of GSK269962A in AML. These data highlight the potential role of ROCK1 as an attractive target for treating AML, as well as the potential of GSK269962A for use in clinical trials of AML.